COMPARISON OF OPTICAL METHODS FOR CHARACTERIZATION OF GLASS MOSAIC WEATHERING - Vladimir Kocour; Veronika Petranova; Jaroslav Valach (Acta Polytechnica CTU Proceedings)
The work presented in this paper is a part of research project supported by Ministry of Culture and devoted to conservation of precious mosaic of "Last Judgement" on St. Vitus Cathedral in Prague. The aim of the project is to enhance external protective polymeric coating on glass tesserae of mosaic and also to develop optical method for assessment of coating’s surface conditions. The paper concentrates on comparison of various methods for surface evaluation assesses their advantages and disadvantages and also discusses their suitability for long term monitoring of coating state, namely reflectometry, scanning probe microscopy, nanoindentation, white-light interferometry, and scanning electron microscopy. It is found that white-light interferometry and reflectometry methods are the most suitable ones for monitoring purposes.